2010
DOI: 10.1002/ange.200907320
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo‐ and Enantioselective Catalytic Tandem Michael Addition/Mannich Reaction: Access to Chiral Isoindolinones and Azetidines with Multiple Stereocenters

Abstract: Michael und Mannich arbeiten zusammen: Ein schneller und verlässlicher Zugang zu hochfunktionalisierten chiralen Isoindolindon‐ und Azetidinderivaten mit mehreren benachbarten Stereozentren wird vorgestellt (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…We envisioned that these chiral diamine ligands, which have unusually rigid structures, would be useful for the construction of a well oriented chiral environment around the metal center, and the corresponding transition metal complexes derived from these chiral diamines could efficiently promote the proposed reaction. Herein, we report a novel copper‐catalyzed asymmetric formal [2+2+2] cycloaddition between one equivalent of ketoester and two equivalents of nitroalkene for the synthesis of cyclohexanes with seven substituents 3ac,ek,l. 10 These compounds are not only important building blocks in organic synthesis, but also represent a structural motif found in a number of important natural and synthetic bioactive products 11.…”
Section: Methodsmentioning
confidence: 99%
“…We envisioned that these chiral diamine ligands, which have unusually rigid structures, would be useful for the construction of a well oriented chiral environment around the metal center, and the corresponding transition metal complexes derived from these chiral diamines could efficiently promote the proposed reaction. Herein, we report a novel copper‐catalyzed asymmetric formal [2+2+2] cycloaddition between one equivalent of ketoester and two equivalents of nitroalkene for the synthesis of cyclohexanes with seven substituents 3ac,ek,l. 10 These compounds are not only important building blocks in organic synthesis, but also represent a structural motif found in a number of important natural and synthetic bioactive products 11.…”
Section: Methodsmentioning
confidence: 99%
“…HFIPA ( 1 e q uiv ) R 1 = Ph , R 2 = R 3 = H , X = O: 85%, 97% ee R 1 = p -BrC 6 H 4 , R 2 = R 3 = H , X = O: 86%, 94% ee R 1 = p -ClC 6 H 4 , R 2 = R 3 = H , X = O: 88%, 94% ee R 1 = m-ClC 6 H 4 , R 2 = R 3 = H , X = O: 81%, 91% ee R 1 = o-FC 6 H 4 , R 2 = R 3 = H , X = O: 86%, 93% ee R 1 = p -Tol , R 2 = R 3 = H , X = O: 80%, 96% ee R 1 = p -MeOC 6 H 4 , R 2 = R 3 = H , X = O: 87%, 94% ee R 1 = m-Tol , R 2 = R 3 = H , X = O: 78%, 92% ee R 1 = 2-Na p h, R 2 = R 3 = H , X = O: 88%, 94% ee R 1 = ( E ) -PhCH=CH , R 2 = R 3 = H , X = O: 83%, 71% ee R 1 = Ph , R 2 = H , R 3 = Me , X = O: 82%, 97% ee R 1 = p -ClC 6 H 4 , R 2 = H , R 3 = Me , X = O: 75%, 96% ee R 1 = p -F 3 CC 6 H 4 , R 2 = H , R 3 = Me , X = O: 83%, 97% ee R 1 = p -Tol , R 2 = H , R 3 = Me , X = O: 78%, 93% ee R 1 = m-Tol , R 2 = H , R 3 = Me , X = O: 75%, 93% ee R 1 = Ph , R 2 = Me , R 3 = H , X = O: 81%, 97% ee R 1 = p -BrC 6 H 4 , R 2 = Me , R 3 = H , X = O: 86%, 95% ee R 1 = p -ClC 6 H 4 , R 2 = Me , R 3 = H , X = O: 84%, 96% ee R 1 = p -Tol , R 2 = Me , R 3 = H , X = O: 80%, 94% ee R 1 = m-Tol , R 2 = Me , R 3 = H , X = O: 76%, 96% ee R 1 = Ph , R 2 = R 3 = H , X = NBoc: 92%, 90% ee R 1 = p -BrC 6 H 4 , R 2 = R 3 = H , X = NBoc: 87%, 95% ee R 1 = o-FC 6 H 4 , R 2 = R 3 = H , X = NBoc: 82%, 97% ee R 1 = p -Tol , R 2 = R 3 = H , X = NBoc: 80%, 98% ee In 2010, Huang et al reported the use of a chiral copper complex in situ generated from CuBr and chiral phosphite 68 to promote the asymmetric three-component domino Michael/Mannich reaction between acyclic chalcones 69, achiral N-sulfonyl aldimines 70 and diethylzinc 1a [28]. The process afforded the corresponding chiral β-aminocarbonyl derivatives 71 bearing three contiguous stereocenters with both good to excellent yields (72-99%) and enantioselectivities (87-95% ee) combined with low to high diastereoselectivities (34-90% de), as illustrated in Scheme 21.…”
Section: Domino Reactions Initiated By Aldol-type Reactionsmentioning
confidence: 99%
“…2d Although several synthetic methods for chiral 3‐substituted isoindolinones have been reported over the past two decades, most of them are diastereoselective reactions by using stoichiometric amounts of chiral auxiliaries or chiral starting materials,3 and the development of catalytic asymmetric methods is in high demand. Quite recently, a few catalytic asymmetric approaches have been reported 46. Huang and co‐workers reported a catalytic asymmetric tandem Michael/Mannich/cyclization reaction of Et 2 Zn, chalcone derivatives, and an imine (methyl 2‐[(tosylimino)methyl]benzoate) to form isoindolinone cores 4.…”
Section: Optimization Studiesmentioning
confidence: 99%